Permanent Deformation Assessment of Cold Recycled Asphalt Mixtures - Vanderlei D. Silva; João Paulo C. Meneses; Kamilla Vasconcelos; Liedi L. B. Bernucci (Advances in Materials Science and Engineering)
The objective of this study was to evaluate the behavior in terms of the permanent deformation of four cold recycled asphalt mixtures stabilized with asphalt emulsion and foamed asphalt. The analysis was conducted considering three flow number test procedures adapted for cold recycled mixtures: (i) ABNT NBR 16505 (method A); (ii) adaptation of the FN test for CRAM according to Kim and Lee’s method (method B); (iii) 3D-Move analysis software simulation of pavement structures to address the stress magnitude for the FN test (method C). The influence of the curing process on the performance of the materials was also verified. The study used an extensive database of computed pavement responses from the four different asphalt pavement structures of the experimental section subjected to axial loading of a tandem axle using the 3D-Move pavement response analysis program. The FN results using the 3D-Move data (method C) demonstrated the good mechanical behaviour with respect to permanent deformation of the cold recycled mixtures subject to axial stress and temperature. The method proposed by Kim and Lee (method B) showed little efficacy for the analysis of the CRAMs tested in this work. The ABNT NBR 16505 method (method A), conventionally used for HMA, highlighted the influence of temperature (60°C) on the CRAM mixtures. For all FN test conditions, the curing was a preponderant factor for the performance of cold recycled asphalt mixtures and should be carefully evaluated to simulate the early stage of the mixtures in the field. It is also important to verify the influence of humidity and temperature on the permanent deformation mechanism of cold recycled asphalt mixtures.